Performance Evaluation of AOP/Biological Hybrid System for Treatment of Recalcitrant Organic Compounds - Stanford S. Makgato; Evans M. Nkhalambayausi-Chirwa (International Journal of Chemical Engineering)
Process water from nuclear fuel recovery unit operations contains a variety of toxic organic compounds. The use of decontamination reagents such as CCl4 together with phenolic tar results in wastewater with a high content of chlorophenols. In this study, the extent of dehalogenation of toxic aromatic compounds was evaluated using a photolytic advanced oxidation process (AOP) followed by biodegradation in the second stage. A hard-to-degrade toxic pollutant, 4-chlorophenol (4-CP), was used to represent a variety of recalcitrant aromatic pollutants in effluent from the nuclear industry. A UV-assisted AOP/bioreactor system demonstrated a great potential in treatment of nuclear process wastewater and this was indicated by high removal efficiency (>98%) under various 4-CP concentrations. Adding hydrogen peroxide (H2O2) as a liquid catalyst further improved biodegradation rate but the effect was limited by the scavenging of OH• radicals under high concentrations of H2O2.